Corps vivante - Delporte, Julie (Éditions Pow Pow, 2022)
"En 1990, Julie Delporte n'a encore jamais vu de butch, mais sa tante préférée chasse et fume le cigare. Presque vingt ans plus tard, elle publie un livre sur Tove Jansson dans lequel elle raconte avec joie que cette artiste finlandaise est la première femme à qui elle s'identifie, seulement elle était lesbienne et pas Julie. À 35 ans, après avoir surligné de toutes les couleurs son exemplaire de La pensée straight de Monique Wittig, Julie Delporte arrête de porter des robes et prend son avenir en main. Dans ce roman graphique qui fait suite à Moi aussi je voulais l'emporter, l'autrice retrace l'histoire de sa sexualité. Une histoire marquée par la violence malheureusement trop banale des agressions, comme par celle des clichés et des injonctions liés à une culture de la performance et de l'hétéronormativité."--
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; amériques; approches et analyses; arts; arts visuels et médiatiques; autofiction; bande-dessinée; canada; corps; cours; discipline; europe; france; har4600; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; queer; québec; roman graphique; régions géographiques; sexualité; thématiques; violences; études littéraires

Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

Impact féministe sur l'art actuel: La Centrale à 40 ans = Feminist impact on contemporary art : La Centrale at 40 - Burisch, Nicole (La Centrale Galerie Powerhouse, 2015)
"Publication, célébrant les 40 ans d'engagement de la Centrale qui se voue au développement de l'histoire des pratiques artistiques féministes et soutient la visibilité d'artistes et d'initiatives moins ou peu représenté-es auprès des institutions culturelles établies"--Page 40.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; montréal; premier cycle; périodes historiques; québec; régions géographiques; sex1911; thématiques

Art et féminisme - Reckitt, Helena; Phelan, Peggy; Reckitt, Helena; Phelan, Peggy (Phaidon, 2011)
Depuis la fin des années 1960, le mouvement féministe a été à l'origine d'innovations, à la fois théoriques et pratiques, qui figurent parmi les plus intéressantes de l'art contemporain. Par ailleurs, certains succès politiques du mouvement féministe ont été obtenus grâce aux artistes, qui ont proposé de nouvelles manières d'envisager les domaines privé et public, l'objet de l'art et son sujet. En soulignant la différence des sexes, le courant féministe a aussi attiré l'attention sur le rôle de l'âge, de la classe sociale, de la race et de la sexualité dans la création artistique et dans sa réception. À la fois critiques et actrices du monde de l'art, les artistes féministes ont donné un nouvel élan à l'art considéré comme démarche à la fois politique et esthétique. Cet ouvrage, conçu par Helena Reckitt, présente les expériences, les idées et les démarches actuelles d'artistes majeures, et met en évidence le lien existant entre les différentes générations d'artistes. L'essai de Peggy Phelan, théoricienne de l'art et de la performance, jette un regard original sur les interprétations classiques de l'art des femmes et propose de nouvelles clés pour comprendre les rapports mouvants entre idées et idéaux du féminisme et pratiques artistiques.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques; théorie de l'art

Global feminisms: new directions in contemporary art - Reilly, Maura; Nochlin, Linda; Brooklyn Museum.; Davis Museum and Cultural Center.; Reilly, Maura; Nochlin, Linda; Brooklyn Museum.; Davis Museum and Cultural Center. (Merrell ;, 2007)
Catalogue for the exhibition Global Feminisms, that took place at the Brooklyn Museum in 2007. The first international exhibition exclusively dedicated to feminist art from 1990 to the present. The show consists of work by approximately eighty women artists from around the world and includes work in all media—painting, sculpture, photography, film, video, installation, and performance. Its goal is not only to showcase a large sampling of contemporary feminist art from a global perspective but also to move beyond the specifically Western brand of feminism that has been perceived as the dominant voice of feminist and artistic practice since the early 1970s.This exhibition is arranged thematically and features the work of important emerging and mid-career artists.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Féminin pluriel et féminismes en arts visuels au Québec - Boileau, Julia (Esse, 2004)
Il y a plus de 20 ans, en tant qu’historienne de l’art, j’avais posé la question à savoir si l’apport des femmes en art contemporain allait changer quelque chose à la pratique artistique et comment, de même qu’à la pratique de la critique et de l’histoire de l’art1. Ce qui suit est une évocation des principaux questionnements que l’art des femmes et les féminismes en art ont amenés au sein de l’art contemporain. La pratique de l’art mais aussi les pratiques muséologiques ont-elles été affectées par l’arrivée en nombre des femmes sur la scène de l’art moderne et contemporain ? La question des femmes recèle-t-elle encore une pertinence dans le monde de l’art contemporain d’aujourd’hui ?
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; art contemporain; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art